Influence of Rift Superposition on Lithospheric Response to East African Rift System Extension: Lapur Range, Turkana, Kenya. Issue 1 (17th January 2018) - Boone, Samuel C.; Seiler, Christian; Kohn, Barry P.; Gleadow, Andrew J. W.; Foster, David A.; Chung, Ling
Abstract: The Turkana Depression of northern Kenya lies at the intersection of the NW‐SE trending late Mesozoic‐early Paleogene South Sudan and Anza rifts and the N‐S trending late Paleogene‐Recent East African Rift System (EARS). A low‐temperature thermochronology study in the Lapur Range reveals a complex tectonothermal evolution related to multiple periods of regional and local tectonism. Zircon (U‐Th)/He data from Precambrian basement record rapid Early Cretaceous denudational cooling. Coeval subsidence in the adjacent Anza and South Sudan rifts (Morley, Bosworth, et al., 1999; Schull, 1988) suggests that the northern Turkana region acted as a basement high separating the grabens, as well as an axial source of sediment. Between ~95 and 90 Ma, a period of reheating commenced with burial of Lapur basement beneath ~500 m of Late Cretaceous‐Eocene Lapur Sandstone and ~1.5–3.5 km of latest Eocene‐early Miocene Turkana volcanics. Apatite fission track (AFT) and apatite (U‐Th‐Sm)/He data record a transition to rapid denudational cooling in the mid‐Miocene (~14 Ma) in response to EARS‐related extension in the northern Turkana Basin. Thermal history models indicate that the Lapur Range experienced ~90–100°C of mid‐Miocene to Plio‐Pleistocene cooling, yielding the first Neogene AFT ages reported from Kenya related to EARS exhumation. We attribute the larger magnitude of cooling in the Lapur Range compared to other regions of the EARS to the attenuated crustal thickness and elevated heat flow of the Turkana Depression, crustal properties inherited from earlier Cretaceous‐Paleogene rifting. The resulting low effective elastic thickness of the Turkana lithosphere allowed for increased isostatic footwall uplift in response to EARS extension. Key Points: Data and modeling show Early Cretaceous (between 100 and 120 Ma) and rapid middle Miocene‐Recent cooling episodes Latter period of cooling marks middle Miocene onset of East African Rift System (EARS) extension in northern Turkana Basin Low effective elastic thickness and high heat flow of Turkana lithosphere amplified isostatic footwall uplift in response to EARS extension